PROBLEM-BASED LEARNING METHODS - Zuxro Rustamova (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
Teaching came into its own as a profession in the last century. Central to this process was the emergence of the concept of methods of language teaching. The method concept in language teaching-the notion of a systematic set of teaching practices based on a particular theory of language and language learning-is a powerful one, and the quest for better methods preoccupied teachers and applied linguists throughout the 21st century. Low authority of a subject because of shortages of a present technique of teaching.